French stereotypes on the basis of belles-lettres - O V Shipilova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
The article presents the typical national-psychological features peculiar to the French nation. The author analyses ethnic features of Frenchmen, including national, social and individual traits, within the framework of the french belles-lettres.